1990
DOI: 10.1111/j.1365-2559.1990.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining of antral gastrin cells is quantitatively increased in Helicobacter pylori gastritis

Abstract: 1990) Histopathology 16, 151-1 55 Immunostaining of antral gastrin cells is quantitatively increased in Hellobacter pylori gastritisThe amount of gastrin-like immunostaining in gastrin degrees of infection were immunostained for gastrin. (G) cells of the antral mucosa was quantified using a Twenty-five G cells from each patient were measured computer-assisted method of measuring immunoreacboth subjectively and by image analysis. Gastrin-like tion product. Biopsies from 2 5 patients without Helioimmunoreactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…6 21-25 Studies of antral biopsies from H pylori infected individuals have shown that gastrin synthesis is increased. 26 ''Overall, our data are consistent with the notion that the major defect leading to enhanced gastrin concentrations is related to disruption of the inhibitory effect of somatostatin on the G cell''…”
Section: Discussionsupporting
confidence: 88%
“…6 21-25 Studies of antral biopsies from H pylori infected individuals have shown that gastrin synthesis is increased. 26 ''Overall, our data are consistent with the notion that the major defect leading to enhanced gastrin concentrations is related to disruption of the inhibitory effect of somatostatin on the G cell''…”
Section: Discussionsupporting
confidence: 88%
“…Sankey et al. (28) demonstrated significantly elevated G cell density in the mucosa of infected patients. He also found the G cells of infected patients to have increased immunoreactivity compared with those of healthy controls, suggesting that cell hyperactivity may be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding G cells and Hp gastritis in adults indicate that, although gastrin cell function may be augmented by Hp infection, G cell counts are not increased (34,35). However, in children with Hp gastritis, G cells have recently been reported to be increased (15).…”
Section: Discussionmentioning
confidence: 99%